Analysis of Factors Influenching Economic Growth in Indonesia 2014 - 2018 - Setiawan, Dedy (Universitas Negeri Semarang, 2024)
It is essential to build more equitable economic growth, which reflects the increased role of regions and the empowerment of all people, by focusing on the efficiency and sustainability of the use of natural resources and the living environment. The study explores factors that influence economic growth, such as exports, imports, investments, and labor wages, to identify the most influential aspects in boosting economic growth in Indonesia between 2014 and 2018. This research uses a literature review analysis tool to analyse the factors that influenced economic growth in Indonesia during the 2014–2018 period. By referring to various relevant literature sources, we evaluated and synthesised the main findings related to Indonesia's economic growth during that period. Research results show that exports have a positive impact on economic growth, while imports have no significant impact. Investments also do not have a significant impact on economic growth, while wages have a positive impact on economic growth. Thus, the study shows that exports and labor wages played an important role in Indonesia's economic growth between 2014 and 2018.